The Effect of Metformin on Female Rats' Bronchial Smooth Muscle in Isolated Organ Bath - Sayin, Orhan; Bozyil, Ahmed Sait; Atli, Ayse Akmese; Pervin, Mehtap; Oz, Zeynep Dila; Hekim, Munevver Gizem; Kacar, Emine (Wiley, 2023)
[Abstract Not Available]
Keywords: Bronchus; Constriction; Isolated organ bath; Metformin; Rat